Motives of training and sport routine highly qualified athletes of 5-a-side blind football national sport team of Russia - Popenko, K. (Sports, Health and Exercise Medicine, 2020)
This article presents the results of studies on the motivation of highly qualified athletes involved in Paralympics sport football five-a-side, which was held at the international friendly tournament in Silvi Marina (Italy) in June 2018. The main factors determining the importance of results in achieving the results are physical and mental stresses corresponding to critical values. The study of sports motivation of qualified Paralympics football players of the national team of the Russian Federation began with the definition of a list of motives for playing football five-a-side (sports of the blind). Analysis and generalization of literary sources made it possible to form an extended circle of motivation, and interviewing and questioning current athletes and coaches, allowed to determine the list of motives of highly qualified athletes, included in the questionnaire for study. The study involved active athletes of the youth and main staff of the Russian national team. Football players represented three regions: Moscow, Moscow Region, and the Republic of Mari El. In total, 13 respondents took part in the survey. The data obtained were statistically processed using the method of average values (calculations were performed using the standard Microsoft Excel for Windows software package).